Пошаговое объяснение:
(x + 3 8/9) - 4 7/18 = 8 19/30 - 2 17/45;
Переведем дроби с целым числом в неправильные дроби. и приведем к общему знаменателю:
(х + 35/9) - 79/18 = 259/30 - 107/45;
х + 35/9 - 79/18 = 777/90 - 214/90;
х + 70/18 - 79/18 = 563/90;
х - 9/18 = 563/90;
х - 1/2 = 563/90;
х = 563/90 + 1/2;
х = 563/90 + 45/90;
х = 608/90;
(608/90 + 3 8/9) - 4 7/18 = 8 19/30 - 2 17/45;
(608/90 + 35/9) - 79/18 = 259/30 - 107/45;
(608/90 + 350/90) - 79/18 = 777/90 - 214/90;
958/90 - 79/18 = 563/90;
958/90 - 395/90 = 563/90;
563/90 = 563/90.
Пошаговое объяснение:
(n-3\8)*8\35=2 2\5-2 2\7
(n-3\8)*8\35=2 14\35-2 10\35
(n-3\8)*8\35=4\35
(n-3\8)=4\35:8\35
(n-3\8)=4\35*35\8
(n-3\8)=1\2
n=1\2+3\8
n=4\8+3\8
n=7\8